A Scalable Biomimetic Synthesis of Resveratrol Dimers and Systematic Evaluation of their Antioxidant Activities1. (29th January 2015) - Matsuura, Bryan S.; Keylor, Mitchell H.; Li, Bo; Lin, YuXuan; Allison, Shelby; Pratt, Derek A.; Stephenson, Corey R. J.
Abstract: An efficient synthetic route to the resveratrol oligomers quadrangularin A and pallidol is reported. It features a scalable biomimetic oxidative dimerization that proceeds in excellent yield and with complete regioselectivity. A systematic evaluation of the natural products and their synthetic precursors as radical‐trapping antioxidants has revealed that, contrary to popular belief, this mode of action is unlikely to account for their observed biological activity.